RECOMMENDATIONS FOR INCREASING THE FINANCIAL CAPACITY OF COMMUNITIES ON THE BASIS OF INCREASING TAX REVENUES - SHAPOVAL, GALYNA; CHEKH, NATALIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The purpose of the paper is to study the tax potential of UTC based on study of financial revenues to the budgets of UTC of Kharkiv region, the reasons for lack of funding and to develop recommendations to increase the financial capacity of UTC based on increased tax revenues. Main sources of UTC budgets have been analyzed in the paper, reasons for possible underfunding of UTC funding due to unused opportunities to receive tax revenues have been identified and recommendations for increasing the financial capacity of communities based on increasing tax revenues have been developed. Taking into account the results of analysis of the current state of financial support for the development of territorial communities, the importance and problems of components of the system of financial support for the development of territorial communities, one of the logical directions is to strengthen the tax base of local governments. In particular, it is advisable to provide in UTC a rule that establishes the procedure for payment of personal income tax at the place of residence of the taxpayer, which will create more favorable conditions for citizens and for the development of social infrastructure of UTC. Another area of tax revenues growth to the budgets of territorial communities is the implementation of land decentralization, which will allow communities to implement their decisions throughout the territory. The community will decide for itself what to do with the land - to cultivate its own farm, rent it out or look for investors.